Factors Determining Youth’s Recreational Behaviour and its Effects on Body Mass Index (BMI) - Zulkia, Dwi Rizka; Zainol, *Rosilawati; Zainol, Norlelawati; Nordin, Nikmatul Adha; Ahmad, Faizah (Journal of Surveying, Construction and Property, 2014)
Youth require recreational activities to enhance their physical and mental health. This study seeks to identify the determinants of youth’s recreational behaviour and effects to their body mass index by built environmental factors. A pilot study was carried out to determine the physical activity, the sedentary behaviour, accessibility and safety of recreational park, and its association with youth body weight index. Respondents comprise of 30 youth aged between 15 to 16 years, randomly selected from a few secondary schools in Subang Jaya, Selangor. Physical activity and sedentary behaviour were measured using the Physical Activity Questionnaire for Adolescents (PAQ-A) and the Adolescent Sedentary Activity Questionnaire (ASAQ). Body mass index (BMI) on the other hand, was computed by measuring the height and weight of the respondents. Accessibility and safety of recreational park were also assessed. The findings reveal that almost half of the respondents have a normal BMI, while 33.3% were severely thin and 20.0% were overweight and obese. For physical activity, most of the respondents stated that they play futsal on both weekday (60.0%) and weekend (46.7%). For sedentary behaviour, watching television is the best choice for respondents to spend their leisure time, about 100.0% on weekday and 86.7% on weekend. There is a modest relationship between BMI and youth who play futsal. Two factors were identified as the reasons for not going to the park which are lack of playing facilities and perception of safety and crime. This study demonstrates the need of youth to be healthy and physically active by playing sport at the park as their recreational activities. Support in terms of proximity of the parks from their home and the provision of sufficient facilities influence youth’s recreational activities.